Designing MOOC Support for University Students: A Case Study From 2022–2024 - Černý, Michal (Pedagogika, 2025)
The study analyses the experiences of learners who have taken part in a university course with a MOOC (massive open online course) component and provides practical insights that MOOC have a place in formal education and are associated with a sense of freedom, autonomy, and empowerment for university students. At the same time, however, to complete them, they need to acquire specific experiences and skills related to time management, self-management, and learning competencies.